SHO Algorithm Based PID Controller for Automatic Generation Control of Multiarea Multiunit Power System With Renewable Energy Source - Patel, Nimai Charan; Yadav, Sujesh Kumar; Yadav, Sunil Kumar; Pradhan, Partha Sarathi (2022 International Conference on Intelligent Controller and Computing for Smart Power (ICICCSP), 2022)
For good quality power delivery to the consumers and maintaining the system stability in an interconnected power system, automatic generation control (AGC) plays a substantial role. This article describes AGC of a multi-area multi-unit interconnected power system (IPS). It consists of three area nine-unit system in which thermal and hydro plants are common in each area and wind, diesel and gas plants are combined in the area 1, area 2 and area 3 respectively. Boiler dynamics (BD), governor dead band (GDB) and generation rate constraint (GRC), are considered to make the system more practical and realistic but due to the introduction of GRC and GDB, the system becomes highly nonlinear. Hence, it becomes a challenging task to stabilize the system against any load disturbance. In this article, proportional-integral-derivative (PID) controller is designed by independently employing particle swarm optimization (PSO) and selfish herd optimization (SHO) algorithm and implemented for AGC of three un-equal area multi-source power system against a load disturbance of 1 % in area 1. It is found that the proposed SHO based PID controller is superior and more effective than the PSO based PID controller in damping out the frequencies and tie-line powers oscillations.